Repackaging “traditional” architecture of the African Village in Zimbabwe - Saidi, Umali (IntechOpen, 2019)
Repackaging is being done through construction of buildings with connections to traditional architecture as well as respective traditional naming of such symbolizing a return to African values. Naming of spaces and buildings is closely tied to the architecture of African heritage. This chapter explores the architecture of selected outdoor spaces in Zimbabwe. It is argued that the new places symbolize, represent African culture in terms of homage, food, hospitality, and cultural security. Furthermore, it is argued the spaces offer an eyrie of cultural values as housed in the architecture as well as names of the spaces thus communicating African sensibilities, aura of the traditional village at the same time sustainably conserving the architecture authored as by African heritage. One of the conclusions made is that the urban landscape can store and communicate African heritage; interestingly requisite architecture can be used in this endeavor. Data were gathered qualitatively, and participant observations, interviews and extensive desktop research were involved.